EFEKTIFITAS PENGGUNAAN BAHASA PADA INSTRUKSI KESELAMATAN DI KONSTRUKSI TWIN TOWER UPN ”VETERAN” JAWA TIMUR - Gunawan, Rizal; Aljabar, Muhammad; Raffif, Jericho Waliudin; Wibowo, Mukti; Wardana, Agus Setiawan Kusuma; Sholihatin, Endang (Jurnal Membaca Bahasa dan Sastra Indonesia, 2024)
Occupational safety is paramount in construction, particularly in large-scale projects like the construction of the UPN "Veteran" East Java Twin Towers. Safety instructions play a crucial role in conveying essential information about hazards and their prevention to workers. Proper comprehension and adherence to these instructions are vital for minimizing the risk of workplace accidents.This study aims to: 1) Evaluate the effectiveness of language use in safety instructions at the construction site of the UPN "Veteran" East Java Twin Towers. 2) Identify the grammatical structure employed in safety instructions at the construction site of the UPN "Veteran" East Java Twin Towers. 3) Formulate recommendations for enhancing the effectiveness of language use in safety instructions at the construction site of the UPN "Veteran" East Java Twin Towers.The study employs a mixed-methods approach, encompassing both quantitative and qualitative methodologies. Data collection involves utilizing Google Forms and document analysis. The study's respondents include construction workers, supervisors, project managers, and students.Furthermore, the study employs a descriptive analysis technique based on the "General OHS Regulations" document issued by PT. PP. The study commenced on April 20, 2024, and lasted for three days.Key findings of the study are as follows: 1) The language used in safety instructions at the construction site of the UPN "Veteran" East Java Twin Towers has been proven effective. This is evident from document analysis and Google Form responses, with 100% of respondents indicating that the sentences used are effective. 2) The grammatical structure employed in safety instructions at the construction site of the UPN "Veteran" East Java Twin Towers includes: a) Clear comprehension (75.5%), b) Accuracy (98.1%), c) Relevance (98.1%), d) Contextual appropriateness (100%)However, there are still some instances of incorrect spelling or non-compliance with EYD (Indonesian Language Spelling Rules). 3) Recommendations for improving the effectiveness of language use in safety instructions at the construction site of the UPN "Veteran" East Java Twin Towers include: a) Revising the writing and spelling of sentences, b) Providing translations for foreign language terms alongside the original text, c) Implementing these measures will enhance comprehension for construction workers.